Kesadaran Wajib Pajak, Kualitas Pelayanan, Sanksi Perpajakan dan Kepatuhan Wajib Pajak Kendaraan Bermotor - Meidy Kantohe; Miryam Lonto; Yosua Gary Pakasi (JRAK: Journal of Accounting Research and Computerized Accounting, 2023)
Motor vehicle tax is a potential source of local tax revenue for the Minahasa district because the number of vehicles registered at the SAMSAT Tondano Joint Office is increasing every year. However, this has not been proportional to the increase in the number of taxpayers paying motor vehicle taxes. This study aims to determine the effect of taxpayer awareness, service quality and tax sanctions on taxpayer compliance in paying motor vehicle taxes at the SAMSAT Tondano office. The method used in this study is a quantitative research method with a population of 107,383 taxpayers whose vehicles are registered at the SAMSAT Tondano Joint Office. The sampling technique uses Accidental Sampling, namely taxpayers who coincidentally meet researchers at the SAMSAT Tondano Joint Office. The number of samples is calculated using the slovin formula and the number of samples obtained is 100 taxpayers. The data analysis technique uses multiple linear regression analysis with the help of SPSS version 29 software. The results of this study indicate that taxpayer awareness, service quality and tax sanctions have a significant effect on taxpayer compliance in paying motor vehicle taxes at the SAMSAT Tondano Joint Office.